Gelucire: An alternative formulation technological tool for both sustained and fast release of drugs in treating diabetes mellitus type ii disease - Upadhyay P.; Pandit J.K.; Wahi A.K. (My University, 2025)
Gelucire is the family of vehicle derived from mixtures of mono-, di-and tri-glycerides with PEG esters of fatty acids. They have a wide variety of application in pharmaceutical formulations. These are used in the preparation of fast release and sustained release formulations. In order to increase the bioavailability of drugs, the residence time of the orally administered dosage form in the upper GIT needs to be prolonged. The main approaches to prolonging the gastric residence time of pharmaceutical dosage forms includes density control delivery system, which float on gastric fluid and an asset to treat Diabetes type II. Gastro retentive solid dispersion could be achieved of poorly soluble drug Glibenclamide with the help of polyethylene glycol and Gelucire 50/13. On the other hand sustained release gastroretentive multiparticulates of metformin hydrochloride could be achieved using Gelucire 39/01 and 43/01 grades. Further both formulations can be explored individual as well as in combination for improved bioavailability by their pharmacokinetic and pharmacodynamic evaluation in wistar rats.